Indigenous People as Self-Narratives of Canada For Building Ontological Security in the Arctic - Dal, Adnan (My University, 2021)
The understanding of traditional security is undergoing a more multi-faceted transformation. Security itself is no more regarded as being limited to a physical presence, it requires a stable self as well. Claiming this, ontological security theory enables scholars to examine state behavior which strengthens identity values via self-narratives. This study aims to reveal that the traditional security perception of Canadian governments is limited in evaluating their relations with the Arctic states and indigenous people, therefore, in recent years, the relevant governments have provided Canadian ontological security in the Arctic region by constructing indigenous people as self-narratives. Therefore, in this paper, instead of traditional national security, it is mentioned that ontological security theory better articulates the state behavior of Canada both domestically and internationally. In the study, the qualified document analysis method is used by examining the reports that include the indigenous peoples as a significant part of Canada's national identity and the declarations announced at the ministerial meetings of the Arctic Council after the chairmanship of Canada. In this way, the study concludes by mentioning that Canada has built its ontological security by constructing self-narratives from indigenous peoples to have a robust position in the Arctic.
Keywords: Çevre Çalışmaları; Uluslararası İlişkiler